2019
DOI: 10.1016/j.jceh.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acids in Hepatic Encephalopathy

Abstract: TX 76504, USA and y Central Texas Veterans Healthcare System, Temple, TX 76504, USA Hepatic encephalopathy describes the array of neurological complications that arise due to liver insufficiency and/or portal-systemic shunt. The pathogenesis of hepatic encephalopathy shares a longstanding association with hyperammonemia and inflammation. Recently, aberrant bile acid signaling has been implicated in the development of key features of hepatic encephalopathy due to acute liver failure including neuronal dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 56 publications
(75 reference statements)
1
14
0
Order By: Relevance
“…Bile acids were quantified from 111 post-mortem brain samples from the dorsolateral prefrontal cortex of AD, MCI and CN individuals in the ROSMAP study Expressed in brain (https://www.synapse.org/#!Synapse:syn10235594) (Supplementary file 2). Although the genes involved in production of cholic acid were not expressed in the brain samples, detection of cholic acid from the metabolomics analysis suggested that cholic acid might enter the brain from the periphery as previously shown in other studies 20,28,29 . We compared the levels of primary and secondary bile acids in individuals with CERAD score of 1-4, where 1, 2, 3 and 4 indicate definitive AD, probable AD, possible AD and no evidence of AD, respectively.…”
Section: Metabolomics Analysis Of Post-mortem Brain Samples To Identisupporting
confidence: 62%
“…Bile acids were quantified from 111 post-mortem brain samples from the dorsolateral prefrontal cortex of AD, MCI and CN individuals in the ROSMAP study Expressed in brain (https://www.synapse.org/#!Synapse:syn10235594) (Supplementary file 2). Although the genes involved in production of cholic acid were not expressed in the brain samples, detection of cholic acid from the metabolomics analysis suggested that cholic acid might enter the brain from the periphery as previously shown in other studies 20,28,29 . We compared the levels of primary and secondary bile acids in individuals with CERAD score of 1-4, where 1, 2, 3 and 4 indicate definitive AD, probable AD, possible AD and no evidence of AD, respectively.…”
Section: Metabolomics Analysis Of Post-mortem Brain Samples To Identisupporting
confidence: 62%
“…Although the genes involved in the production of CA were not expressed in the brain samples, the detection of CA from the metabolomics analysis suggested that CA may enter the brain from the periphery, as previously shown in other studies. 20 , 28 , 29 We compared the levels of primary and secondary BAs in individuals with a Consortium to Establish a Registry for Alzheimer's Disease (CERAD) score of 1–4, in which 1, 2, 3, and 4 indicate definitive AD, probable AD, possible AD, and no evidence of AD, respectively. The ratio of primary conjugated and secondary BAs with respect to CA showed that deoxycholic acid (DCA), lithocholic acid (LCA), glycochenodeoxycholate (GCDCA), CDCA, taurodeoxycholic acid (TDCA), glycodeoxycholic acid (GDCA), ursodeoxycholic acid (UDCA), allolithocholate (alloLCA) and taurocholic acid (TCA) were higher in individuals with AD (CERAD score 1–3) compared to controls ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The brain microenvironment loses stability, followed by BBB dysfunction. Moreover, multiple factors disturb the CNS function, including changes in brain structure, neurotransmitters, and other substance concentrations, leading to cognitive impairments in HE ( Jones, 2003 ; Banks, 2006 ; Dhanda and Sandhir, 2015 ; Jayakumar and Norenberg, 2018 ; DeMorrow, 2019 ).…”
Section: Neuroinflammation and Immune Regulationmentioning
confidence: 99%
“…However, bile acid levels were found to be increased in the cerebrospinal fluid, while toxic bile acids accumulated in the brains of the BDL mouse models. Therefore, nervous system disorders are associated with the toxic effects of bile acids in HE ( Weiss et al, 2016 ; DeMorrow, 2019 ).…”
Section: Intestinal Bacteria Metabolites In the Gut–brain Axismentioning
confidence: 99%